Translation and conflict: two narratives of the same coin - Mohammad Ahmad Thawabteh, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
This paper sheds some light on the Palestinian narrative dated from the Israeli occupation of Palestine in 1948, and the birth of the case of the Palestinian refugees driven out from Palestine. Israel has initiated a counter-narrative to that of Palestine. The paper conflates two different notions: the analysis of the narratives that have a bearing on the Palestinian-Israeli conflict and the issue of translation as it affects our understanding of this conflict. The paper shows that the narrative has become important for Palestinian refugees, as it is reminiscent of Nakba ʻthe catastropheʼ which has afflicted them since then and the Israelis as it has been a metaphor for the long-awaited Jewish state. The paper explores possible avenues for translators to take a greater part as participants in the construction of social and political reality when dealing with contesting narratives.